Evaluating Drought Tolerance in African Rice Genotypes Across Upland and Lowland Ecologies in Nigeria - Sow, A.; Oluwatosin, A.O.; Semwal, V.K. (2025)
Rice is a staple for over half the world’s population. However, its productivity is severely limited by drought stress. In this study, we screened 16 upland and 25 lowland genotypes under well-watered (WW) and drought stress (DS) conditions. Grain yield was strongly and positively correlated with vegetative vigor, panicle dry weight, harvest index, chlorophyll content, and Quantum yield of Photosystem II under DS in both the environments. Many upland genotypes maintained high yields under drought ~1637-2242 kg/ha compared to ~2016-3629 kg/ha under WW. The most promising lowland genotypes yielded ~2600-2900 kg/ha under DS compared to 4600-6300 under WW. Among the five genotypes that were tested in both upland and lowland conditions, two performed well in both environments, suggesting adaptability to both ecologies. Some genotypes showed high post-drought recovery (up to ~90%), indicating that they are suitable for border testing in drought prone environments to check stability and potential lines useful for breeding drought tolerance in rice.